Stent placement above the sphincter of Oddi permits implementation of neoadjuvant chemotherapy in patients with initially unresectable Klatskin tumor - Kubota, Kensuke; Hasegawa, Sho; Iwasaki, Akito; Sato, Takamitsu; Fujita, Yuji; Hosono, Kunihiro; Nakajima, Atsushi; Mori, Ryutaro; Matsuyama, Ryusei; Endo, Itaru (Endoscopy International Open, 2016)
Background and study aims: Neoadjuvant chemotherapy (NAC) may lead to a successful margin-negative resection in patients with initially unresectable locally advanced Klatskin tumor (IULAKT). Use of removable plastic stents is preferable for the safe implementation of NAC in patients with IULAKT to reduce the risk of recurrent cholangitis. Our aim was to evaluate the efficacy associated with the use of plastic stents placed across the stenosis and above the papilla (above stent) during NAC. Patients and methods: In this study, we stratified the patients into two groups chronologically with respect to the period of stent placement: above stent group (n = 17) and across stent group (n = 23) (plastic stent across the sphincter of Oddi). Results: The median stent patency period was 99 days in the above stent group and 31 days in the across stent group (P < 0.0001). The number of stents (P = 0.017) and the rate of emerging undrained cholangitis areas (P = 0.025) were significantly reduced in the above stent group than the counterpart. Regarding time to recurrent biliary obstruction, the above stent group had a longer duration than the across stent group (log rank test, P = 0.004). Length of hospital stay was significantly shorter for the above stent group than the across stent group (P = 0.0475). Multivariate analysis revealed that above stent placement (odds ratio = 33.638, P = 0.0048) was significantly associated with stent patency over a period of 90 days. Conclusions: Above stent placement should be considered for the relief of biliary obstruction and potentially reduces the cost for patients with IULAKT scheduled to receive NAC.